DEVELOPMENT OF UNIFIED PROCEDURES FOR FINANCIAL INSTITUTIONS IN ORDER TO PREVENT MONEY LAUNDERING AND TERRORISM FINANCING - Kalinina, Suzanna (Administrative and Criminal Justice, 2019)
The relevance of the topic is confirmed by the changes taking place in the financial monitoring system: the expansion of the financial monitoring range of procedures complication´s supervisory bodies aimed at countering money laundering and financing of terrorism, the creation of specialized international and European requirements, which causes changes in the legal regulation of public relations in this area, both at the level of the Estonian Republic, and at international level. Taking into account these changes, financial institutions are a subject to significant legal risks. The purpose of this topic is to improve the financial institution risk management system, in the field of anti-money laundering and countering financing of terrorism. The theoretical and methodological basis of the study are the provisions and conclusions regarding anti-money laundering and countering financing of terrorism risk management issues contained in the research works of different Estonian and Russian authors; as well as the author analysed anti money laundering and counter terrorism financing legal acts and revealed the main recommendations to financial institutions for preventing money laundering and terrorism financing. The author analyses reasons, which affect licenses withdrawal due to breach of money laundering. The nature of the tasks and the system approach to their solution determined the use of the following research methods in the research: analysis and synthesis, grouping and classification, scientific generalization, expert assessments and graphical analysis.